An open-label, phase I study of the polo-like kinase-1 inhibitor, BI 2536, in patients with advanced solid tumors - Hofheinz, Ralf-Dieter; Al-Batran, Salah-Eddin; Hochhaus, Andreas; Jäger, Elke; Reichardt, Volker L.; Fritsch, Holger; Trommeshauser, Dirk; Munzert, Gerd (Clinical cancer research, 2010)
Purpose: This phase I, open-label, dose-escalation study investigated the maximum tolerated dose (MTD) of BI 2536, a small-molecule polo-like kinase (Plk)-1 inhibitor, in two treatment schedules in patients with advanced solid tumors. Secondary objectives included evaluation of safety, efficacy, and pharmacokinetics.Experimental Design: Patients received a single i.v. dose of BI 2536 as a 1-hour infusion on days 1 and 8 or a single 24-hour infusion on day 1 of each 21-day treatment course. MTD determination was based on dose-limiting toxicities.Results: Forty-four and 26 patients received each treatment schedule, respectively. The MTD of BI 2536 in the day 1 and 8 schedule was 100 mg per administration (200 mg per course). The MTD for the second dosing schedule was not determined; a 225-mg dose was well tolerated. The most frequently reported treatment-related nonhematologic adverse events were gastrointestinal events and fatigue. Hematotoxicity as the most relevant side effect was similar in both schedules; neutropenia grades 3 and 4 were observed in 16 patients (36.4%) of the day 1 and 8 schedule and 13 patients (50%) of the 24-hour infusion. Fourteen patients (32%) treated in the day 1 and 8 dosing schedule had a best overall response of stable disease. Plasma concentrations of BI 2536 increased dose proportionally, with no relevant accumulation of exposure in the day 1 and 8 dosing schedule. The average terminal half-life was 50 hours.Conclusions: BI 2536 administered in either treatment schedule has adequate safety in patients with advanced solid tumors, warranting further clinical investigation of polo-like kinase-1 inhibitors. Clin Cancer Res; 16(18); 4666-74. ©2010 AACR.
Gesehen am 14.03.2023